Structural stability analysis of rain trees (Samanea saman) subjected to dead, live, and wind loads combination - SITI CHUROTUL AINI; ULFA ADZKIA; EFFENDI TRI BAHTIAR; M. MIFTAH RAHMAN; AGUS BUONO; LINA KARLINASARI (Society for Indonesian Biodiversity, 2024)
Abstract. Aini SC, Adzkia U, Bahtiar ET, Rahman MM, Buono A, Karlinasari L. 2024. Structural stability analysis of rain trees (Samanea saman) subjected to dead, live, and wind loads combination. Biodiversitas 25: 3899-3908. Tree failure can arise from factors associated with load resistance and structural stability at sites of environmental growth. In this study, an investigation was conducted into the structural analysis of standing trees, considering the combination of compression and flexure loads in the adoption of building code guidelines. The objective of this study is to determine the safety factor based on a combined load combination governing the Euler and Ylinen Buckling Stress Method. The study used 50 rain trees (Samanea saman (Jacq.) Merr.). Therefore, to assess the impact of various load combinations on standing trees, including dead, live, and wind loads, three analyses were performed: (1) D + L + W, (2) D + L, and (3) D only. The dead load (D) represents the weight of the crown and stem above the observed section, the live load (L) accounts for activities such as climbing or hanging, and W represents wind loads. The D + L + W load combination induced both compression and bending stresses on the trees, whereas the D + L and D only focused on compression loads. Determining the minimum critical height is crucial in assessing the safety factor and categorizing trees into three groups: unsafe, safe, and very safe. The results indicated that the combined load of D + L + W demonstrated that the minimum critical height resulted from the superposition of compression and bending stresses. This finding underscores the significant role of the wind in the safety of standing trees. Structural stability analysis revealed that 18 trees were unsafe, 30 were safe, and 2 were classified as very safe. This research contributes valuable insights into understanding tree biomechanics and tree characteristics, offering a distinct approach compared to existing methods.